2017
DOI: 10.1016/j.janxdis.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive bias modification of interpretation in children with social anxiety disorder

Abstract: HighlightsChildren with social anxiety disorder were assigned to CBM-I training or no training.We measured the effects on interpretation bias and social anxiety.CBM-I was not associated with greater change in interpretations than no training.Social anxiety symptoms and diagnoses were not influenced by CBM-I training.More intensive CBM-I training may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…The impact of participants' awareness of intervention intentions on CBM-I efficacy remains unclear, with some evidence suggesting this knowledge enhances bias modification and symptom change (Mobini et al, 2014), while others found it to hinder treatment effects (Orchard, Apetroaia, Clarke, & Creswell, 2017). Firstly, the design did not include qualitative assessments at debriefing, thus participants' awareness of the study's intentions is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of participants' awareness of intervention intentions on CBM-I efficacy remains unclear, with some evidence suggesting this knowledge enhances bias modification and symptom change (Mobini et al, 2014), while others found it to hinder treatment effects (Orchard, Apetroaia, Clarke, & Creswell, 2017). Firstly, the design did not include qualitative assessments at debriefing, thus participants' awareness of the study's intentions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the design did not include qualitative assessments at debriefing, thus participants' awareness of the study's intentions is unknown. The impact of participants' awareness of intervention intentions on CBM-I efficacy remains unclear, with some evidence suggesting this knowledge enhances bias modification and symptom change (Mobini et al, 2014), while others found it to hinder treatment effects (Orchard, Apetroaia, Clarke, & Creswell, 2017). Future efforts should look to include quantitative and/or qualitative awareness checks to determine the relationship between awareness and CBM-I efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Second, of the 26 studies included in the current meta‐analysis, 20 were conducted with nonanxious individuals. Only three were conducted among clinically anxious participants (Fu, Du, Au, & Lau, ; Klein et al., ; Orchard, Apetroaia, Clarke, & Creswell, ) and four with participants scoring above average on an anxiety measure (Fu, Du, Au, & Lau, ; Vassilopoulos, Blackwell, Misailidi, Kyritsi, & Ayfanti, ; Vassilopoulos et al., ; White et al., ). Although our exploratory analyses did not reveal significantly greater effects of CBM‐I on anxious individuals compared to unselected samples, this may reflect the small number of studies included and it remains plausible that greater effects of CBM‐I on anxiety will be obtained among individuals with clinical levels of anxiety symptoms where there is more potential for change.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, participants with high social anxiety showed a negative interpretation bias for the verbal scenarios only, with no bias for the nonverbal scenarios. This negative interpretation bias for verbal scenarios mirrors the findings of negative interpretation bias in other studies of socially anxious youth (Haller et al, 2016;Miers et al, 2008;Orchard, Apetroaia, Clarke, & Creswell, 2017) and adults (Amir et al, 2005;Dryman & Heimberg, 2015;Giannini & Loscalzo, 2016;Huppert et al, 2003;Kanai, Sasagawa, Chen, Shimada, & Sakano, 2010), as well as other health issues in youth and adult populations such as depression (Eley et al, 2008;Holmes, Lang, & Shah, 2009;Normansell & Wisco, 2017) and chronic pain (see review by Lau et al, 2018). Speaking is regarded as a performance-based social situation whereby the manner and content of one's verbal delivery can be judged by listeners, whereas non-speaking social situations may not necessarily subsume such listener evaluation.…”
Section: Social Anxiety Influenced Interpretations For Both Groupssupporting
confidence: 83%